Morphological characteristics and electrical properties analysis of silica based on river and coastal iron sand - Meiliyadi, Lalu Ahmad Didik; Wahyudi, Muh.; Damayanti, Isniwana; Fudholi, Ahmad (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
This study aims to analyze silica's morphological characteristics and electrical properties based on the river and coastal sand. Iron samples were taken from Sompang river sand, East Lombok and Coastal Sand from Gading, Mataram City. The silica was synthesized using the sol-gel method with a sintering temperature variation of 100 to 175 ℃. Morphological characteristics samples analysis was done using SEM-EDX. The electrical properties of iron sand included measuring the dielectric constant using the parallel plate method. Furthermore, the resistivity was measured using the two-point probe method. In the silica-based on river sand sample, the resistivity value was inversely proportional to the sintering temperature. In contrast, the resistivity value of silica based on the coastal sand sample was directly proportional to the sintering temperature. Silica-based on river sand has a resistivity of about 7.1'104 Wm at a sintering temperature of 100℃ and 3.5'104 Wm at a sintering temperature of 175℃. Silica-based on river sand has a resistivity of about 1.8'104 Wm at a sintering temperature of 100℃ and 7.1'104 Wm at 175℃. This research is a preliminary study on the electrical properties of natural sand-based silica to improve understanding of the physical properties of silica to be used in technological applications, such as sensors. Furthermore, the dielectric constant value in the river sand sample was directly proportional to the sintering temperature. However, the dielectric constant in the coastal sand sample was inversely proportional to the sintering temperature. Silica-based on river sand has a dielectric constant of about 1.02'102 at a sintering temperature of 100℃ and 1.18'102 at 175℃. Silica-based on coastal sand has a dielectric constant of about 1.97'102 at a sintering temperature of 100℃ and 1.15'102 at 175℃.